The Decentralized Non-Fungible Token Exchange with Secure Connections - Sharath, M.S.; Shreedhara N, Hegde; Lai, Mei Yoon (INTI International University, 2024)
During the COVID-19 outbreak, due to the lockdown, all museums and galleries were closed for more than a year. So, the buying and selling of physical arts have dropped. This project aims to overcome this challenge by developing a decentralized application called Decentralized NFT Exchange. The decentralized non-fungible token (NFT)exchange includes features such as secure wallet connections, NFT creations, buying, selling, and profile management. The back-end of the decentralized NFT exchange is implemented using Solidity-based smart contracts, while InterPlanetary File System (IPFS)is used for decentralized storage. Front-end development of decentralized NFT exchange is implemented using React JSX and framework web3.js that helps developers connect to the Ethereum network. Decentralized NFT can help art creators sell their artworks using a smart contract system where the ownership of the work will become the property of the new owner with proof of a digital certificate. The project demonstrates the practical application of blockchain technology in developing decentralized applications (DApps)for secure and decentralized digital asset management. Overall, Decentralized NFT might be a solution for the copyright of work in the future and the project contributes to secure and decentralized digital asset management